Spatial interactions - Jun Sung Kim; Eleonora Patacchini; Pierre M. Picard; Yves Zenou (Quantitative Economics, 2023)
This paper studies how the strength of social ties is affected by the geographical location of other individuals and their social capital. We characterize the equilibrium in terms of both social interactions and social capital. We show that lower travel costs increase not only the interaction frequency but also the social capital for all agents. We also show that the equilibrium frequency of interactions is lower than the efficient one. Using a unique geocoded data set of friendship networks among adolescents in the United States, we structurally estimate the model and show that indeed agents socially interact less than that at the first best optimum. Our policy analysis suggests that, at the same cost, subsidizing social interactions yield a higher total welfare than subsidizing transportation costs.
Keywords: D85; R23; Z13; 330; Social networks; location; structural estimation; policies